Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To find the inverse of the function [tex]\( f(x) = 2x + 1 \)[/tex], we need to follow several specific steps:
1. Rewrite the Function's Equation:
Let's begin with the function:
[tex]\[ y = f(x) = 2x + 1 \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
To find the inverse function, we swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]. This leads to:
[tex]\[ x = 2y + 1 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
Now, solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ x = 2y + 1 \][/tex]
Subtract 1 from both sides to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ x - 1 = 2y \][/tex]
Divide both sides by 2 to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{x - 1}{2} \][/tex]
4. Express the Inverse Function:
The expression [tex]\( y = \frac{x - 1}{2} \)[/tex] is the inverse of the original function. Thus, we can write:
[tex]\[ h(x) = \frac{x - 1}{2} \][/tex]
5. Simplify the Inverse Function:
Simplifying [tex]\( h(x) = \frac{x - 1}{2} \)[/tex] gives:
[tex]\[ h(x) = \frac{1}{2} x - \frac{1}{2} \][/tex]
Given the four choices:
1. [tex]\( h(x) = \frac{1}{2} x - \frac{1}{2} \)[/tex]
2. [tex]\( h(x) = \frac{1}{2} x + \frac{1}{2} \)[/tex]
3. [tex]\( h(x) = \frac{1}{2} x - 2 \)[/tex]
4. [tex]\( h(x) = \frac{1}{2} x + 2 \)[/tex]
The correct inverse function is:
[tex]\[ h(x) = \frac{1}{2} x - \frac{1}{2} \][/tex]
Therefore, the inverse of the function [tex]\( f(x) = 2x + 1 \)[/tex] is:
[tex]\[ h(x) = \frac{1}{2} x - \frac{1}{2} \][/tex]
Which corresponds to the first choice. Hence, the answer is:
[tex]\[ \boxed{1} \][/tex]
1. Rewrite the Function's Equation:
Let's begin with the function:
[tex]\[ y = f(x) = 2x + 1 \][/tex]
2. Swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]:
To find the inverse function, we swap [tex]\( x \)[/tex] and [tex]\( y \)[/tex]. This leads to:
[tex]\[ x = 2y + 1 \][/tex]
3. Solve for [tex]\( y \)[/tex]:
Now, solve for [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex]:
[tex]\[ x = 2y + 1 \][/tex]
Subtract 1 from both sides to isolate the term with [tex]\( y \)[/tex]:
[tex]\[ x - 1 = 2y \][/tex]
Divide both sides by 2 to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{x - 1}{2} \][/tex]
4. Express the Inverse Function:
The expression [tex]\( y = \frac{x - 1}{2} \)[/tex] is the inverse of the original function. Thus, we can write:
[tex]\[ h(x) = \frac{x - 1}{2} \][/tex]
5. Simplify the Inverse Function:
Simplifying [tex]\( h(x) = \frac{x - 1}{2} \)[/tex] gives:
[tex]\[ h(x) = \frac{1}{2} x - \frac{1}{2} \][/tex]
Given the four choices:
1. [tex]\( h(x) = \frac{1}{2} x - \frac{1}{2} \)[/tex]
2. [tex]\( h(x) = \frac{1}{2} x + \frac{1}{2} \)[/tex]
3. [tex]\( h(x) = \frac{1}{2} x - 2 \)[/tex]
4. [tex]\( h(x) = \frac{1}{2} x + 2 \)[/tex]
The correct inverse function is:
[tex]\[ h(x) = \frac{1}{2} x - \frac{1}{2} \][/tex]
Therefore, the inverse of the function [tex]\( f(x) = 2x + 1 \)[/tex] is:
[tex]\[ h(x) = \frac{1}{2} x - \frac{1}{2} \][/tex]
Which corresponds to the first choice. Hence, the answer is:
[tex]\[ \boxed{1} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.